EFEKTIFITAS TEHNIK GYM BALL TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III - Siti Ni’amah; Sri Hadi Sulistiyaningsih (Jurnal Kebidanan, 2024)
Back pain during pregnancy usually occurs due to stretching of the bones, especially in the waist area which corresponds to increasing gestational age. Back pain often occurs because the mother's points and balance change from their original condition (Andarmoyo and Suharti, 2013). If back pain is not treated properly, it can cause the pregnant woman's quality of life to worsen. This problem will continue in the form of recurring injuries or appear continuously in worse conditions according to the course of the pregnancy (Kantonis, 2017). Gym Ball is physical therapy or simple exercises using a ball, where these exercises are applied to pregnant women, giving birth mothers and post-natal mothers. The benefits of using a gym ball are that it increases blood flow to the uterus, placenta and baby, relieves pressure and can provide comfort for the knees and ankles, helps reduce back pain in pregnant women and makes it easier for pregnant women to move. (Kurniawati, 2017) This study aims to determine the effect of the gym ball technique on back pain in third trimester pregnant women. The type of research used is pre-experimental design research with a one group pretest posttest design. The population and sample in the study were 15 TM III pregnant women with a gestational age of 32 weeks taken using the total sampling technique. The results showed that the average frequency of back pain before the intervention was 1.00 with a standard deviation of 0.791 and the average frequency of back pain after the intervention was 0.29 with a standard deviation of 0.470. The correlation results between the two variables produce a figure of 0.673 with a p value = 0.003. This shows that there is a strong relationship with a significant level of p value <0.05. The results of the research show that the correlation in reducing the level of back pain is 0.8, which shows a very strong and positive relationship and has a significant level at the <0.05 level, meaning it is highly correlated. This shows that there is an effect of the gymball technique on reducing the level of back pain. Keywords: Gym Ball technique, reduction of back pain, third trimester pregnant women